Impact of clinical versus radiographic progression on clinical outcomes in metastatic castration-resistant prostate cancer. Issue 6 (12th November 2020) - Rao, Arpit; Scher, Howard I; De Porre, Peter; Yu, Margaret K; Londhe, Anil; Qi, Keqin; Morris, Michael J; Ryan, Charles
Abstract : Objectives: Unequivocal clinical progression (UCP)—a worsening of clinical status with or without radiographic progression (RAD)—represents a distinct mode of disease progression in metastatic prostate cancer. We evaluated the prevalence, risk factors and the impact of UCP on survival outcomes. Methods: A post-hoc analysis of the COU-AA-302, a randomised phase 3 study of abiraterone plus prednisone (AAP) versus prednisone was performed. Baseline characteristics were summarised. Cox proportional-hazards model and Kaplan-Meier method were used for survival and time to event analyses, respectively. Iterative multiple imputation method was used for correlation between clinicoradiographic progression-free survival (crPFS) and overall survival (OS). Results: Of 736 patients with disease progression, 280 (38%) had UCP-only and 124 (17%) had UCP plus RAD. Prognostic index model high-risk group was associated with increased likelihood of UCP (p<0.0001). Median OS was 25.7 months in UCP-only and 33.0 months for RAD-only (HR 1.39; 95% CI 1.16 to 1.66; p=0.0003). UCP adversely impacted OS in both treatment groups. Lowest OS was seen in patients with prostate specific antigen (PSA)-non-response plus UCP-only progression (median OS 22.6 months (95% CI 20.7 to 24.4)). Including UCP events lowered estimates of treatment benefit—median crPFS was 13.3 months (95% CI 11.1 to 13.8) versus median rPFS of 16.5 months (95% CI 13.8 to 16.8) in AAP group. Finally, crPFS showed high correlation with OS (r=0.67; 95% CI 0.63 to 0.71). Conclusions: UCP is a common and clinically relevant phenomenon in patients with metastatic castration-resistant prostate cancer (mCRPC) treated with AAP or prednisone. UCP is prognostic and associated with inferior OS and post-progression survival. A combination of PSA-non-response and UCP identifies patients with poorest survival. When included in PFS analysis, UCP diminishes estimates of treatment benefit. Continued study of UCP in mCRPC is warranted.